Bismuth Oxyhalide-Based Materials (BiOX: X = Cl, Br, I) and Their Application in Photoelectrocatalytic Degradation of Organic Pollutants in Water: A Review - Castillo-Cabrera, G. Xavier; Espinoza-Montero, Patricio J.; Alulema-Pullupaxi, Paulina; Mora, José Ramón; Villacís-García, Milton H. (Frontiers in Chemistry, 2022)
An important target of photoelectrocatalysis (PEC) technology is the development of semiconductor-based photoelectrodes capable of absorbing solar energy (visible light) and promoting oxidation and reduction reactions. Bismuth oxyhalide-based materials BiOX (X = Cl, Br, and I) meet these requirements. Their crystalline structure, optical and electronic properties, and photocatalytic activity under visible light mean that these materials can be coupled to other semiconductors to develop novel heterostructures for photoelectrochemical degradation systems. This review provides a general overview of controlled BiOX powder synthesis methods, and discusses the optical and structural features of BiOX-based materials, focusing on heterojunction photoanodes. In addition, it summarizes the most recent applications in this field, particularly photoelectrochemical performance, experimental conditions and degradation efficiencies reported for some organic pollutants (e.g., pharmaceuticals, organic dyes, phenolic derivatives, etc.). Finally, as this review seeks to serve as a guide for the characteristics and various properties of these interesting semiconductors, it discusses future PEC-related challenges to explore.